Pengaruh Konten Komunikasi Instagram @studiodjiwa terhadap Persepsi Pengikut dalam Meningkatkan Kesadaran Kesehatan Mental - Nadifa Zahra Hasbullah; Lathifa Prima Ghanistyana; Sabrina Setyaningtyaz; Mas Siti Syakira; Muhammad Defran Ikhsan (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze the influence of content published by @studiodjiwa Instagram accounts on followers' perceptions in increasing mental health awareness. The background of this research departs from the phenomenon of increasing use of social media, especially Instagram, as a means of delivering mental health information among the young generation of Indonesia. The approach used was quantitative with a correlational design, involving 101 respondents who were followers of the account. Data was obtained through questionnaires that measured the intensity of social media use and perception of the mental health content presented. The results showed a very strong relationship between communication content and follower perception, with a correlation coefficient value of 0.925 and a contribution of 85.5% to perception variation. These findings were analyzed using persuasive communication theory, social construction, perceptual theory, and digital health communication as a theoretical basis. This research makes an important contribution to mental health practitioners and digital content creators in designing more effective, informative, and engaging communication strategies. In the midst of the development of the digital era, the results of this study confirm the importance of using social media as an educational tool that has a positive impact on increasing awareness of mental health.